Maternal and congenital syphilis in Indigenous Peoples: a scoping review of the worldwide literature - Andrey Moreira Cardoso; Aline Diniz Rodrigues Caldas; Evelin Santos Oliveira; Enny Santos Paixão; Maria Auxiliadora Santos Soares; Idália Oliveira dos Santos; Maurício Lima Barreto; Maria Yury Travassos Ichihara (BMC, 2023)
Abstract Background Syphilis is among the most common sexually transmitted infections worldwide. When it occurs during pregnancy, it can seriously affect the fetus and newborn`s health. The scarcity of studies on maternal and congenital syphilis in Indigenous Peoples remains an obstacle to its control in these populations. This study aimed to explore the breadth of the literature, map updated evidence, and identify knowledge gaps on maternal and congenital syphilis in Indigenous Peoples worldwide. Methods We conducted a Scoping review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses - Extension for Scoping Reviews. In March 2021, we collected data through a priority search on PubMed, Web of Science, Embase, and SciELO. Results The strategy yielded 24 studies for analysis. Data in the articles were collected from 1989 to 2020, half from 2015 onwards. Studies were in Oceania and the Americas, mainly in South America (66.7%), particularly in Brazil (50.0%). The topics assessed were Data quality related to maternal and congenital syphilis (20.8%); Diagnosis, provision, access, and use of health services (62.5%); Disease frequency and health inequities (54.2%); Determinants of maternal syphilis and congenital syphilis (20.8%); and Outcomes of maternal and congenital syphilis in the fetus (20.8%). The results show that the available literature on maternal and congenital syphilis is sparse and concentrated in some geographic areas; the frequency of these diseases in Indigenous Peoples varies but is generally higher than in the non-indigenous counterparts; the quality of surveillance data and health information systems is poor; multiple healthcare barriers exist; and the diversity of terms to identify Indigenous Peoples is a challenge to mapping scientific outputs on Indigenous Peoples' health. Conclusions Maternal and congenital syphilis in Indigenous Peoples is a double-neglected condition and research in this area should be given the priority and encouragement it deserves globally. Reliable data and improving access to health care are needed to reduce the burden of syphilis and correctly inform policies and health services response to mitigate ethnic-racial inequalities in maternal and congenital syphilis.